Ectopic tissue engineered ligament with silk collagen scaffold for ACL regeneration: A preliminary study. (15th April 2017) - Ran, Jisheng; Hu, Yejun; Le, Huihui; Chen, Yangwu; Zheng, Zefeng; Chen, Xiao; Yin, Zi; Yan, Ruijian; Jin, Zhangchu; Tang, Chenqi; Huang, Jiayun; Gu, Yanjia; et al.
Graphical abstract: Abstract: Anterior cruciate ligament (ACL) reconstruction remains a formidable clinical challenge because of the lack of vascularization and adequate cell numbers in the joint cavity. In this study, we developed a novel strategy to mimic the early stage of repair in vivo, which recapitulated extra-articular inflammatory response to facilitate the early ingrowth of blood vessels and cells. A vascularized ectopic tissue engineered ligament (ETEL) with silk collagen scaffold was developed and then transferred to reconstruct the ACL in rabbits without interruption of perfusion. At 2 weeks after ACL reconstruction, more well-perfused cells and vessels were found in the regenerated ACL with ETEL, which decreased dramatically at the 4 and 12 week time points with collagen deposition and maturation. ACL treated with ETEL exhibited more mature ligament structure and enhanced ligament-bone healing post-reconstructive surgery at 4 and 12 weeks, as compared with the control group. In addition, the ETEL group was demonstrated to have higher modulus and stiffness than the control group significantly at 12 weeks post-reconstructive surgery. In conclusion, our results demonstrated that the ETEL can provide sufficient vascularity and cellularity during the early stages of healing, and subsequently promote ACL regeneration and ligament-bone healing, suggesting its clinic use as a promising therapeutic modality. Statement of Significance: Early inflammatory cell infiltration, tissue and vessels ingrowth were significantly higher in the extra-articular implanted scaffolds than theses in the joint cavity. By mimicking the early stages of wound repair, which provided extra-articular inflammatory stimulation to facilitate the early ingrowth of blood vessels and cells, a vascularized ectopic tissue engineered ligament (ETEL) with silk collagen scaffold was constructed by subcutaneous implantation for 2 weeks. The fully vascularized TE ligament was then transferred to rebuild ACL without blood perfusion interruption, and was demonstrated to exhibit improved ACL regeneration, bone tunnel healing and mechanical properties.